LANGUAGE OF CAMPAIGN COMMUNICATION MARKETING COMMUNICATION THROUGH BRANDING: ANALYSIS OF THE CREATIVE WORKERS OF TOURISM INDUSTRY IN WEST SUMATRA - Fitri Adona; Arni Utamaningsih; Buyung Sidik (International Conference on Languages and Arts, 2014)
Marketing West Sumatra is conventionally considered less effective because it is poorly understood by investors and have not been able to save the region from poverty. The main factors associated with the marketing of this area are: (1) the value of the product and how to communicate it, and (2) branding communication. The local government has failed to build the value of the product if the product is offered only in the form of a promise that is not in accordance with reality. Therefore, local governments must build a brand on the products it offers. A good brand is able to bind to the consumer, have an emotional connection with consumers, easy to understand, easy to remember and can be trusted. In fact, sometimes the government managed to create a brand of the product, but fails to communicate it to the market. The first year of this study intends to look at the effectiveness of marketing communications campaigns through branding of West Sumatra government communication in overcoming poverty. This study was conducted over two years, the first year in the area to help define and communicate its brand well and advised marketing campaign to communicate the various potential regions to the consumer market and investors; and the second year is planned to evaluate whether the offender is already powerful marketing area and was able to reduce poverty? In evaluating marketing communication activities, the analysis was conducted on the activity of the market, competitive conditions, and analysis of the target audience to get detailed information. Such information will assist in planning your next marketing communication programs. The evaluation plan is divided into two criteria, namely the pre-test and post-test. With the study of local government is expected to increase the number of investors and solve the problem of poverty. Marketing area by itself able to increase empowerment, partnership, participation and social advocacy become a strategy in overcoming poverty. Keyword: marketing campaigns, brand, poverty